FAKTOR KESULITAN BELAJAR GAMBAR TEKNIK MAHASISWA PRODI PENDIDIKAN TEKNIK BANGUNAN FT-UNP - Pardianto Yudistira Pangaribuan; Drs. Juniman Silalahi, M.Pd (CIVED, 2019)
Abstract—This study began with the implementation of student learning Image Engineering Buildings experienced problems in using applications in which some students have less ability and are slow to do tasks. This study aims to reveal how student learning can be fulfilled properly if students' learning difficultiin terms of internal factors and external factors. This type of research is descriptive. This research was conducted on students majoring in Building Image Engineering with the number of respondents 32 students. Research data in the form of primary data obtained directly from respondents with instruments in the form of questionnaires arranged on a Likert scale with four scales. The results of the study show that in the sub-factor internal factors, indicators of biological factors are in the sufficient category and indicators of psychological factors are also in the sufficient category which means that student learning has not been fulfilled properly. For sub-variables of external factors, indicators of family factors and school factors are in the sufficient category which means that student learning has not been fulfilled properly, while the factor indicators of society are in the which means that student learning is not well fulfilled.Keywords: Difficulty of Learning, Students,  Engineering Drawings.